Automatic detection of selective arterial devices for advanced visualization during abdominal aortic aneurysm endovascular repair. Issue 10 (October 2015) - Lessard, Simon; Kauffmann, Claude; Pfister, Marcus; Cloutier, Guy; Thérasse, Éric; de Guise, Jacques A.; Soulez, Gilles
Highlights The centre of pigtail radiopaque markers can be accurately segmented. The surface of the visible part of the delivery device can be segmented with a sensitivity of 85.9%. The less visible part of the delivery device can be traced with an accuracy of 0.74 mm. The automatic reshaping of vascular structure based on endovascular tools detection is therefore possible.